Effects of the high-molecular excipients on optimization of the pharmacokinetic properties of drugs - P. . Bochkov; G. . Kolyvanov; A. . Litvin; V. . Zherdev; R. . Shevchenko (LLC "Publisher OKI", 2020)
Applying of different natural and synthetic excipients as in developing of drug forms as manufacturing various drug delivery systems was shown.